Paracoccidioidomycosis: A comparative study of the evolutionary serologic, clinical and radiologic results for patients treated with ketoconazole or amphotericin B plus sulfonamides - Marques, Silvio Alencar [UNESP]; Dillon, N. L.; Franco, M. F. [UNESP]; Habermann, M. C.; Lastoria, Joel Carlos [UNESP]; Stolf, Hamilton Ometto [UNESP]; Marcondes, J.; Grizzo, W.; Silva, N. C A; Cavariani, M. R.; Curi, P. R. (Springer Nature, 1985)
A comparative study of two groups of patients with paracoccidioidomycosis was carried out with the objective of comparing the evolutionary serologic, clinical and radiologic results after 6, 12, 15 and 18 months of treatment with ketoconazole (22 patients) or amphotericin B plus sulfonamides (32 patients). The serologic data analyzed as a whole showed a tendency to sharper drops in antibody titers in the patients treated with ketoconazole. Clinically patients treated with ketoconazole fared better but the differences were not statistically significant. No statistical difference was detected between groups in terms of the results of radiologic evolution. © 1985 Martinus Nijhoff/Dr W. Junk Publishers.
Keywords: amphotericin b; antibody; hydrocortisone acetate; hydrocortisone sodium succinate; ketoconazole; sulfadimethoxine; sulfadoxine; sulfonamide; clinical article; drug mixture; drug therapy; fungus; human; mycosis; south american blastomycosis; therapy; Adolescent; Adult; Aged; Amphotericin B; Child; Drug Evaluation; Drug Therapy, Combination; Female; Humans; Ketoconazole; Male; Middle Aged; Paracoccidioidomycosis; Sulfadimethoxine; Sulfadoxine; Sulfonamides; Fungi